The Effects of Covid 19 on Workers and Its Implications on Socio-Economic Inequalities in Ghana - Braimah, Mohammed Kamarideen; Titigah , Gregory Titigah (International Journal of Health Sciences, 2023)
Purpose: The novel coronavirus has caused havoc to the various economies throughout the world with Ghana, not an exception. The purpose of this paper is to ascertain the effects of the COVID-19 pandemic on the various institutions and sectors in Ghana particularly the effects on Ghanaian workers and its implications on inequalities in Ghana be studied. Methodology: The paper adopted a qualitative research approach and used discourse analysis of secondary data obtained from sources such as journal articles, online news articles, newspaper publication and other internet sources. The study is hinged on the institutional theory. Findings: The findings indicated that the outbreak of the pandemic have brought negative consequences to the workers of the country. These consequences are loss of jobs, reduced income and source of livelihoods. Unique Contribution to Theory, Policy and Practice: The policies implemented by the government of Ghana to curtail the spread of the virus have rather exacerbated the already troubling inequality situation in the country. There is also a widening gender inequality, income and poverty inequality, employment inequality, and inequality in the access to education between the vulnerable and less vulnerable in Ghanaian society.